Biosafety, and improvement of osteoporosis in cage layers through using chOPG protein - Hou, Lele (Saudi J Biol Sci, 2020)
Thirty six 56-week-old ISA cage layers were divided into two groups randomly. The cage layers in control group (12 birds) and experiment group (24 birds) were respectively injected with 300 µL sodium chloride and 300 μg eucaryon recombinant plasmid pcDNA3.1(+)-chOPG. Eighty 56-week-old ISA cage layers were divided into group A, B, C and D randomly. Group A is for control group, while plasmid pcDNA3.1(+)-chOPG was injected to B, C, D groups in muscle at the dosage of 200 μg, 400 μg, 600 μg at 57, 59, 61, 63th weeks respectively. After the detection on the expression of chOPG protein after 3 h, it reached the peak at 7 d and then fell down. After 28 d, nothing was detected in the injected skeletal muscles. The other organs did not express exogenous chOPG protein. Plasmid in liver had the fastest metabolism. The pathological effects in main organs were not observed by histological section. The concentration of plasma calcium in B, C and D groups significantly decreased, while the activity of alkaline phosphatase was significantly improved, compared to control group. The total average value of abnormal and broken eggs of group C, D was significantly higher than those of group A. The bone biomechanical property and bone radiographic density of tibia and femur in experiment group were significantly higher than control group. Therefore, one conclusion is drawn that the expression of chOPG from foreign plasmid pcDNA3.1(+)-chOPG have contribute to bone formation, chOPG can increase bone density and strength by inhibiting bone resorption. Nevertheless, it was cleared out from cellular system in a short-term after intramuscular injection and cannot integrate into host chromosome genomic in cage layers. There were no pathological effects observed in the main tissues. It is believed that 200 μg plasmid pcDNA3.1(+)-chOPG should be within the safe range for application, because it can improve bone metabolism and will not affect the production of cage layer during the post cycle.